EXPLORING AI AS YOUR ENGLISH LEARNING PARTNER: PELATIHAN PEMANFAATAN APLIKASI KECERDASAN BUATAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA SMK TELKOM PEKANBARU - Silvia Utami; Jumerli Ariati (Smart Education, 2025)
Abstract: community service activity was conducted based on a request from SMK Telkom Pekanbaru to provide training on utilizing Artificial Intelligence (AI), specifically the ELSA Speak and Gliglish applications. These applications were introduced as a creative solution to enhance students' English language skills, particularly speaking proficiency. The training targeted 42 students from the Office Management, Accounting, and Hospitality majors. ELSA Speak and Gliglish, accessible via smartphone, were used as personalized learning aids to practice speaking skills relevant to the world of work. The main objective was to equip students with the ability to independently use AI tools for English conversation practice, ensuring they are better prepared for professional communication needs after graduation, aligning with the demands of the industry 4.0 era. The training utilized a Participatory Action Research (PAR) approach through an interactive seminar conducted in three sessions, focusing on guided practice and immediate feedback mechanisms provided by AI. The overall evaluation, conducted using a satisfaction questionnaire, showed the activity achieved a